Day 1 Mon, November 09, 2015 2015
DOI: 10.2118/177417-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Based Scale Inhibitors for Seawater Injection Operations in High-Salinity Formation Water Reservoirs

Abstract: Water flooding using seawater is a major oil filed operation implemented in different carbonate and sandstone reservoirs to maintain reservoir pressure and enhance oil recovery. However, due to the high sulfate content in the injected seawater, significant calcium, barium and strontium sulfate scale deposition can occur and cause severe formation damage. Typically, scale inhibitors are applied in the field to prevent the formation of calcium sulfate scale where they act either as chelating agents to form a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition to phosphates and phosphonates inhibitor, polymeric inhibitors have been used extensively. These inhibitors are based on different function groups such as polymaleic acid (PMA), polyacrylic acid (PAA), polyphosphino carboxylic acid (PPCA) (Obied et al 2015). Currently, the addition of water-soluble polymers are also widely used and proved as effective scale inhibitors in oil fields (Can and Üner 2015;Huang et al 2019;Liu et al 2017).…”
Section: Polymer-based Scale Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to phosphates and phosphonates inhibitor, polymeric inhibitors have been used extensively. These inhibitors are based on different function groups such as polymaleic acid (PMA), polyacrylic acid (PAA), polyphosphino carboxylic acid (PPCA) (Obied et al 2015). Currently, the addition of water-soluble polymers are also widely used and proved as effective scale inhibitors in oil fields (Can and Üner 2015;Huang et al 2019;Liu et al 2017).…”
Section: Polymer-based Scale Inhibitorsmentioning
confidence: 99%
“…On the contrary, the permeability of the core plug in core-flooding based adsorption experiment indicated that no formation damage has been recorded. The differential pressure is maintained at 20 psi (Obied et al 2015) (Table 3).…”
Section: Carboxymethyl Cellulose (Cmc)mentioning
confidence: 99%
“…All of these factors are potential sources of injection decline. Obied (2015) performed geochemical analysis on the injected water after processing. Typical injected chemistry can be seen in Table 1 below.…”
Section: Injected Water Quality Monitoringmentioning
confidence: 99%